Buying Agreements of Small Islands to Foreign Citizens from an Agrarian Law Perspective in Indonesia - Damianus Krismantoro (IHSA Institute, 2022)
There are many cases of buying small islands in Indonesia. Moreover, foreign nationals interested in acquiring land in Indonesia often make these purchases. This study then aims to see the causes and background of the buying and selling of small islands in Indonesia to foreign nationals, and the consequences from the perspective of agrarian law. This research is a type of normative juridical research. The approach method used in this research is a statutory approach and a conceptual approach. Researchers will process the research data that has been collected. This study found that many aspects affect the buying and selling of small islands to foreign nationals. From an agrarian perspective, this buying and selling activity causes a change in the status of land rights in the form of usufructuary rights or rental rights. The local government itself is trying to make some regulations to be able to protect these small islands